Genetic and environmental factors affect the onset of type 1 diabetes mellitus. Issue 8 (24th December 2015) - Altobelli, Emma; Petrocelli, Reimondo; Verrotti, Alberto; Chiarelli, Francesco; Marziliano, Ciro
Abstract : Background: Type 1 diabetes mellitus (T1DM) is influenced by genetic as well as environmental factors. Its incidence has risen considerably since the 1950s. Objective: This study investigates T1DM time trends from 1989 to 2008 and tries to establish whether breast/bottle feeding, a family history of diabetes, and childhood infectious diseases influence age at onset. Methods: The study used the population‐based registry of childhood diabetes of Abruzzo (central Italy), which includes incident cases of patients aged less than 15 yr. The pooled 1989–2008 global ascertainment of the registry was 95%. The trend was estimated using age–period–cohort models Results: Overall standardized incidence rates (SIR) increased by 73.38% from 8.94 (1989–1993) to 15.50 (2004–2008). A rising trend was found in all age groups; annual rises were significant for the overall population (3.40%, p < 0.01) and for 5–9 yr olds (5.48%, p < 0.01). SIR increased in males by 106.26%, from 9.26 in 1989–1993 to 19.10 in 2004–2008. Early T1DM onset was related to mixed feeding (6.80 yr ± 3.58 vs 8.20 ± 3.81 yr; p = 0.002), and a family history of T1DM (6.71 ± 3.96 yr vs. 8.09 ± 3.77 yr; p = 0.014), whereas multiple infections delayed age at onset (9.71 ± 2.37 yr vs 7.71 ± 2.82 yr; p = 0.03). Conclusions: T1DM incidence exhibits a rising time trend that is particularly evident in males and in middle age group; mixed feeding and a family history of diabetes are associated with early onset, multiple bacterial infections contracted before diabetes are associated with a significant delay.